Awareness Among Girl Healthcare Students Regarding Physiological Nature of Vaginal Discharge - Bipasha Barat; Sandhya Gadre; Madhulika Dube (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Leucorrhoea also spelled leukorrhoea, as a flow of a whitish, yellow, or greenish discharge from the vagina of the female that may be normal or that may be a sign of infection. Commonly, physiological vaginal discharge is confused with being associated with some pathology. AIMS: The aim of this study was; to estimate the percentage of awareness about physiological nature of vaginal discharge in  MBBS students; Paramedical students and Nursing students, to estimate the percentage of women experiencing vaginal white discharge, estimating the percentage of women/girls who consult doctors because of vaginal white discharge, advising women/ girls with pathological vaginal discharge for consultation. METHODS: The present cross sectional study was done among female students from Medical, Paramedical and Nursing branch of Chirayu Medical College and Hospital, Bhopal. Total number of 246 female students were taken into the study. They were provided with a questionnaire consisting of 30 questions, which was divided into sections of; Awareness, Evaluation, Practice and Knowledge. The answers given by the three groups were compared for studying awareness regarding physiological nature of vaginal discharge. Nature of vaginal discharge experienced by individual students was also evaluated. Comparison of Practices followed by the students in daily life was also done. Knowledge regarding vaginal discharge was studied. RESULTS: Students were scored on basis of their answer in knowledge and awareness; each correct answer awarded 1 point and incorrect answer awarded 0. Unpaired t Test for comparing the Awareness Scores shows significant inter-group variation in awareness. Medical students had significantly higher awareness about vaginal discharge as compared to the other two groups. Further, Awareness of the paramedical group was higher than the nursing group. Overall responses within each group were however homogenous, representing comparable intra-group awareness about vaginal discharge. Similar findings were seen for knowledge scoring. CONCLUSION: It was found that Awareness & knowledge regarding physiological vaginal white discharge is highest in medical students followed by paramedical & nursing students. Nursing students consult doctors the most, medical students consult the least. But the positive and negative attitude towards the discharge is homogeneous in all the groups. A small portion of medical students had never experienced vaginal discharge.